General Arrangement System in Archival Studies and It’s Components - Rukancı, Fatih; Koç, Hasan (Information World, 2010)
In archival science, it is crucial to save and transfer the documents to the next generations and emerging organizations, as well as to organize the document stacks to the use of administrations and of researchers. Without doubt, making effi cient use of nonclassifi ed document stacks and especially getting the needed documents from them are quite diffi cult, even impossible. For this reason, classifi cation type of studies to be carried out in the archives is decisive for rendering effi cient archival services. In the present study, by taking the type and amount of archival documents into account, a general classifi cation system has been devised. Main purposes of the system and its practical applications were tried to be explained. The explanations were supported with examples from Turkey, which actually has a rich archive potential,-in terms of realization of the mentioned type of classifi cation processes within the framework of standard applications.